2004
DOI: 10.1007/s00464-003-9328-x
|View full text |Cite
|
Sign up to set email alerts
|

Open vs thorascopic surgical management of bronchogenic cysts

Abstract: Bronchogenic cyst resection can be performed safely. For complete treatment of these patients, total excision of the wall cyst is needed. In selected patients, the thoracoscopic procedure may decrease the duration of surgical drainage and length of hospital stay without increasing the operating time or MSK for complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 8 publications
(21 reference statements)
5
46
2
1
Order By: Relevance
“…Through review of the English literature, we found that our study was the first article evaluating the benefits of VATS for adults undergoing the excision of MBC by comparing between operation methods. Our data indicated that VATS procedure decrease the duration of chest drainage, which is in consistent with Tolg and colleagues' study (29), and that VATS procedure did not increase the risk of incomplete resection, surgeryrelated complications, duration of intensive care unit stay, and postoperative complications. Moreover, our data also indicated that VATS procedure had a shorter operative time, a shorter postoperative hospital stay, less intraoperative blood loss, and less pleural drainage of the first three days after surgery.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Through review of the English literature, we found that our study was the first article evaluating the benefits of VATS for adults undergoing the excision of MBC by comparing between operation methods. Our data indicated that VATS procedure decrease the duration of chest drainage, which is in consistent with Tolg and colleagues' study (29), and that VATS procedure did not increase the risk of incomplete resection, surgeryrelated complications, duration of intensive care unit stay, and postoperative complications. Moreover, our data also indicated that VATS procedure had a shorter operative time, a shorter postoperative hospital stay, less intraoperative blood loss, and less pleural drainage of the first three days after surgery.…”
Section: Discussionsupporting
confidence: 80%
“…However, most of these studies are case reports or case series, and appropriate comparative data to PLT have been sparse. Until now, only a small case series has evaluated the post-operative outcomes in children undergoing open verse thoracoscopic resection of bronchogenic cysts (29). Through review of the English literature, we found that our study was the first article evaluating the benefits of VATS for adults undergoing the excision of MBC by comparing between operation methods.…”
Section: Discussionmentioning
confidence: 92%
“…The lack of intercostal muscle incision and the lower risk of rib fracture reduce the postoperative pain and when compared to thoracotomy, thoracoscopy reduces the chest tube duration and length of hospital stay [5]. Conversion to thoracotomy is mainly related to major pleural adherence as was the case in our study (7%) similar to those observed in other single center experience [7], and considerably lower than the 35% reported by the French multicenter study [13].…”
Section: Discussionsupporting
confidence: 49%
“…In our series symptoms were present in only 11 patients (37%); asymptomatic patients frequently requested surgical resection because of enlarging cysts, the risk of complication or fear of malignancy. Since the first thoracoscopic excision of bronchogenic cyst reported in 1991 by Mouroux et al [10], many case reports or limited series have been published [5,7,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation